Sodium-ion battery positive electrode material, sodium-ion battery and preparation method of sodium-ion battery positive electrode material

By integrating potassium molybdate into the P2 and O3 phases of sodium-ion batteries through high-temperature sintering, the interlayer spacing is optimized, improving sodium ion conductivity and overall battery performance.

CN119181799APending Publication Date: 2024-12-24SHENZHEN BTR NEW ENERGY TECH RES INST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411247567.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

The different sodium interlayer spacings between P2 and O3 phase materials in sodium-ion batteries result in a short-board effect, limiting the comprehensive improvement of conductivity and performance.

Method used

A sodium-ion battery positive electrode material is developed by incorporating potassium molybdate into a two-phase system of P2 and O3 phases through high-temperature sintering, adjusting the interlayer spacing to enhance sodium ion diffusion and conductivity.

Benefits of technology

The material improves the lattice adaptability, reducing sodium ion diffusion barriers and enhancing the battery's rate and cycle performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119181799A_ABST
    Figure CN119181799A_ABST
Patent Text Reader

Abstract

The invention discloses a sodium-ion battery positive electrode material, a sodium-ion battery and a preparation method of the sodium-ion battery positive electrode material. The sodium ion battery positive electrode material is composed of a sodium layer potassium-containing P2 phase material and a transition metal layer molybdenum-containing O3 phase material, the layer adaptation degree Q of the sodium ion battery positive electrode material is less than or equal to 0.3, and Q = | q1-q2 |; wherein when the sodium ion battery positive electrode material is subjected to XRD (X-Ray Diffraction) test, the angle 2 theta corresponding to the [002] peak of the P2-phase material is q1, and the angle 2 theta corresponding to the [003] peak of the O3-phase material is q2. According to the invention, potassium molybdate is introduced into a two-phase system of a P2 phase and an O3 phase, so that the lattice adaptation degree of the two-phase structure is improved, the problem that the sodium layer spacing of two materials is different is solved, and the performance of the battery in various aspects such as rate, cycle and the like is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a sodium ion battery positive electrode material, a sodium ion battery and a preparation method thereof. Background Art

[0002] At present, there are two main crystal structure materials in the field of sodium-layer oxygen positive electrodes, P2 and O3. Sodium batteries made with each as positive electrode material have different application fields. The P2 phase focuses on cycle and rate performance, while the O3 phase focuses on capacity. The industry has mixed the two materials as positive electrode materials, hoping to have the advantages of each material at the same time. However, due to the different structures, the sodium interlayer spacing of the two materials is different, resulting in different sodium diffusion coefficients, causing a short-board effect in practical applications, that is, the conductivity of sodium ions is based on the weaker side, so that various performances cannot be comprehensively improved in theory. Therefore, it is urgent to solve a series of problems caused by the different sodium interlayer spacing between the P2 phase and the O3 phase. Summary of the invention

[0003] The main purpose of the present invention is to provide a sodium ion battery positive electrode material, a sodium ion battery and a preparation method thereof, so as to overcome the deficiencies of the prior art.

[0004] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes: The embodiment of the present invention provides a positive electrode material for a sodium ion battery, which comprises: a P2 phase material containing potassium in a sodium layer and an O3 phase material containing molybdenum in a transition metal layer, wherein the layer adaptability Q of the positive electrode material for a sodium ion battery is less than or equal to 0.3, and Q=|q1-q2|; In which, when the sodium ion battery positive electrode material is tested by XRD, the

[002] peak of the P2 phase material corresponds to an angle 2θ of q1, and the

[003] peak of the O3 phase material corresponds to an angle 2θ of q2.

[0005] The present invention also provides a method for preparing the aforementioned sodium ion battery positive electrode material, which comprises: At least a nickel-iron-manganese hydroxide precursor, a sodium source, and an M1 source are used as raw materials to prepare an O3-type layered oxide positive electrode material and a P2-type layered oxide positive electrode material; And, the O3 type layered oxide positive electrode material, the P2 type layered oxide positive electrode material and potassium molybdate are mixed and sintered to obtain a sodium ion battery positive electrode material.

[0006] The embodiments of the present invention also provide the use of the aforementioned sodium ion battery positive electrode material in preparing a sodium battery positive electrode or a sodium ion battery.

[0007] An embodiment of the present invention further provides a sodium battery positive electrode, which includes a positive electrode material, a conductive agent, a binder and a current collector; wherein the positive electrode material includes the aforementioned sodium ion battery positive electrode material.

[0008] An embodiment of the present invention further provides a sodium ion battery, which includes the aforementioned sodium ion battery positive electrode material or sodium battery positive electrode.

[0009] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention improves the lattice adaptability of the two-phase structure by introducing potassium molybdate into the two-phase system of the P2 phase and the O3 phase, so that the sodium layer spacing of the two phases in the mixed-phase material is as close as possible, thereby reducing the diffusion barrier of sodium ions in the bulk phase and improving the conduction efficiency of sodium ions; at the same time, the performance of the battery end, i.e., the rate and cycle of the battery, is further improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0011] Figure 1 This is a schematic diagram of the potassium molybdate doping principle in a typical implementation scheme of the present invention; Figure 2 is the XRD pattern of the positive electrode material prepared in Example 1 of the present invention; Figure 3 is the XRD pattern of the positive electrode material prepared in Example 2 of the present invention; Figure 4 is the XRD pattern of the positive electrode material prepared in Example 3 of the present invention; Figure 5 is the XRD pattern of the positive electrode material prepared in Comparative Example 1 of the present invention; Figure 6 It is the XRD diagram of the positive electrode material prepared in Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0012] In view of the defects of the prior art, the inventors of this case have proposed the technical solution of the present invention after long-term research and extensive practice. The present invention adds potassium molybdate to the existing two-phase system of P2 phase and O3 phase for two-stage high-temperature sintering. The first high-temperature section is 850-910 degrees, which is slightly lower than the melting point of potassium molybdate, 919°C. However, due to the mutual melting effect between various substances, potassium molybdate can be initially melted at this time, and the molybdenum therein enters the transition metal layer of the O3 phase material with higher reaction energy. Since the sodium layer of the O3 phase is narrower and the reaction energy of the P2 phase material is lower, the potassium element is still free outside the two-phase positive electrode material; the second high-temperature section is set to 920-1000°C, which is completely higher than the melting point of potassium molybdate. Potassium molybdate is completely melted, and potassium enters the sodium layer of the P2 phase to occupy the vacancy. The schematic diagram is as follows Figure 1 As shown, the Q of the two-phase material after the second sintering is finally achieved to be ≤ 0.3, achieving complementary performance advantages in sodium battery applications.

[0013] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0014] Specifically, as one aspect of the technical solution of the present invention, a sodium ion battery positive electrode material involved therein includes: a sodium layer containing potassium in a P2 phase material and a transition metal layer containing molybdenum in an O3 phase material, wherein the layer adaptability of the sodium ion battery positive electrode material is Q≤0.3, and Q=|q1-q2|; In which, when the sodium ion battery positive electrode material is tested by XRD, the

[002] peak of the P2 phase material corresponds to an angle 2θ of q1, and the

[003] peak of the O3 phase material corresponds to an angle 2θ of q2.

[0015] In some preferred embodiments, the chemical formula of the sodium ion battery positive electrode material is Na x K y (Ni a1 Fe b1 Mn c1 M1 d1 ) 1-d2 Mo d2 O2, wherein (a1+b1+c1+d1)=1, 0.8≤x+y≤0.95, M1 is selected from any one or more combinations of elements selected from Sn, Fe, Al, Nb, Ti, Zr, Sr, Co, Li, K, Mg, Ca, Cu, Zn, 0.25≤a1≤0.4, 0.15≤b1≤0.4, 0.3≤c1≤0.55, 0.01≤d1≤0.05, 0.01≤d2≤0.05, y=2*d2.

[0016] Another aspect of the embodiments of the present invention further provides a method for preparing the aforementioned sodium ion battery positive electrode material, which comprises: At least a nickel-iron-manganese hydroxide precursor, a sodium source, and an M1 source are used as raw materials to prepare an O3-type layered oxide positive electrode material and a P2-type layered oxide positive electrode material; And, the O3 type layered oxide positive electrode material, the P2 type layered oxide positive electrode material and potassium molybdate are mixed and sintered to obtain a sodium ion battery positive electrode material.

[0017] In some preferred embodiments, the preparation method specifically includes: mixing a nickel iron manganese hydroxide precursor, a sodium source and an M1 source and sintering at 850-950° C. for 12-24 hours to obtain an O3 type layered oxide positive electrode material and a P2 type layered oxide positive electrode material; Wherein, the chemical formula of the O3 type layered oxide positive electrode material is Na x Ni a1 Fe b1 Mn c1 M1 d1 O2, 0.80<x≤1.0, 0.25≤a1≤0.4, 0.25≤b1≤0.4, 0.3≤c1≤0.55, 0.01≤d1≤0.05; the chemical formula of the P2-type layered oxide positive electrode material is Na x Ni a1 Fe b1 Mn c1 M1 d1 O2, 0.60≤x≤0.80, 0.25≤a1≤0.4, 0.25≤b1≤0.4, 0.3≤c1≤0.55, 0.01≤d1≤0.05.

[0018] Furthermore, in the present invention, the O3 type and the P2 type are prepared mainly by controlling the amount of sodium.

[0019] Furthermore, the O3-type layered oxide positive electrode material is Na x Ni a1 Fe b1 Mn c1 M1 d1O2 (0.80<x≤1.0, 0.25≤a1≤0.4, 0.25≤b1≤0.4, 0.3≤c1≤0.55, 0.01≤d1≤0.05), the preparation steps are as follows: 1) nickel iron manganese hydroxide precursor, sodium source, M1 source are used as raw materials, and they are fully mixed in proportion to obtain a mixed material; 2) the mixed material is placed in a corundum crucible, and then transferred to a high-temperature box furnace for sintering in a protective atmosphere, and cooled after sintering to obtain the desired O3 type layered oxide sodium ion battery positive electrode material. The calcination conditions are: the first stage sintering temperature is 300-600℃, the sintering time is 2-8h, the second stage sintering temperature is 850~950℃, the sintering time is 12~24h, the heating rate is 3~10℃ / min, and the protective atmosphere is oxygen or air.

[0020] Furthermore, the P2-type layered oxide positive electrode material is Na x Ni a1 Fe b1 Mn c1 M1 d1 O2 (0.60≤x≤0.80, 0.25≤a1≤0.4, 0.25≤b1≤0.4, 0.3≤c1≤0.55, 0.01≤d1≤0.05), the preparation steps are as follows: 1) nickel iron manganese hydroxide precursor, sodium source, M1 source as raw materials, mix according to proportion to obtain a mixed material; 2) the mixed material is placed in a corundum crucible, and then transferred to a high-temperature box furnace for sintering in a protective atmosphere, and cooled after sintering to obtain the required P2 type layered oxide sodium ion battery positive electrode material. The calcination conditions are: the first stage sintering temperature is 300-600℃, the sintering time is 2-8h, the second stage sintering temperature is 850~950℃, the sintering time is 12~24h, the heating rate is 3~10℃ / min, and the protective atmosphere is oxygen or air.

[0021] Furthermore, the nickel-iron-manganese hydroxide precursor is prepared by using any one or more combinations of sulfates, hydrochlorides, nitrates, carbonates, acetates, oxides, sulfides, nitrides, and hydroxides of nickel-iron-manganese ions.

[0022] Further, the sodium source includes any one or more combinations of anhydrous sodium carbonate, sodium carbonate monohydrate, sodium carbonate decahydrate, sodium bicarbonate, and sodium sulfate, but is not limited thereto.

[0023] Further, the M1 source is selected from the corresponding oxides and / or hydroxides of any one or more combinations of Sn, Fe, Al, Nb, Ti, Zr, Sr, Co, Li, K, Mg, Ca, Cu, and Zn, and is not limited thereto.

[0024] In some preferred embodiments, the preparation method specifically includes: uniformly mixing the O3-type layered oxide positive electrode material, the P2-type layered oxide positive electrode material and potassium molybdate, first sintering at 850-910°C for 4-12h, and then sintering at 920-1000°C for 4-12h to obtain the sodium ion battery positive electrode material.

[0025] Furthermore, the mass ratio of the O3-type layered oxide positive electrode material, the P2-type layered oxide positive electrode material and potassium molybdate is 0.2-0.8:0.8-0.2:0.01-0.05.

[0026] In the present invention, the interlayer spacing of the P2 phase itself is larger while that of the O3 phase is smaller. The inventors of this case can achieve different roles in the two phases by doping a certain proportion x of potassium molybdate (K2MO4) in the existing two-phase positive electrode system through high-temperature sintering: the P2 phase is often a sodium-poor phase with a large proportion of sodium vacancies. Therefore, the potassium element in potassium molybdate tends to enter the sodium layer of the P2 phase to occupy some vacancies. The reduction of vacancies reduces the mutual repulsion between sodium atoms on both sides of the sodium layer, resulting in a decrease in the interlayer spacing. The reaction can be reflected in the characterization as the right shift of the

[002] peak of the P2 phase in the XRD test; the system energy of the O3 phase is higher and the formation energy with external substances is lower, so the molybdenum element will preferentially enter the O3 phase structure and achieve doping in the transition metal layer; and the larger ionic radius of molybdenum itself widens the interlayer spacing and increases the C axis, which can be reflected in the characterization as the left shift of the

[003] peak of the O3 phase in the XRD test. Therefore, the layer matching degree Q is defined, the peak angle of the P2 phase

[002] is q1, the peak angle of the O3 phase

[003] is q2, Q=|q1-q2|, and the two-phase material Q≤0.3 is achieved by potassium molybdate doping in the present invention, that is, the interlayer spacing of the two phases can be sufficiently close to achieve complementary performance advantages in the application of sodium batteries.

[0027] Another aspect of the embodiments of the present invention further provides use of the aforementioned sodium ion battery positive electrode material in preparing a sodium battery positive electrode or a sodium ion battery.

[0028] Another aspect of an embodiment of the present invention further provides a sodium battery positive electrode, which includes a positive electrode material, a conductive agent, a binder and a current collector; wherein the positive electrode material includes the aforementioned sodium ion battery positive electrode material.

[0029] In some preferred embodiments, the positive electrode material, the conductive agent and the binder form a positive electrode slurry, and the positive electrode slurry is coated on the surface of the current collector to form a positive electrode of a sodium battery.

[0030] In some preferred embodiments, the mass ratio of the positive electrode material, the conductive agent and the binder is 90-99:0.5-5:0.5-5.

[0031] In some preferred embodiments, the conductive agent includes conductive carbon black, but is not limited thereto.

[0032] In some preferred embodiments, the binder includes any one or more combinations of sodium carboxymethyl cellulose, styrene-butadiene latex, and polyvinylidene fluoride, but is not limited thereto.

[0033] In some preferred embodiments, the current collector is a metal foil, which includes aluminum foil and / or copper foil, but is not limited thereto.

[0034] Another aspect of an embodiment of the present invention further provides a sodium ion battery, which includes the aforementioned sodium ion battery positive electrode material or sodium battery positive electrode.

[0035] The technical solution of the present invention is further described in detail below in conjunction with several preferred embodiments and drawings. This embodiment is implemented on the premise of the technical solution of the invention, and a detailed implementation method and specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments.

[0036] The experimental materials used in the following examples can be purchased from conventional biochemical reagent companies unless otherwise specified. Unless otherwise specified, "room temperature" used in this application refers to the temperature measured by a Celsius thermometer in an ordinary laboratory, generally 20-30°C, preferably 25°C (Kelvin temperature is 298.15K) ± 2°C. Embodiment 1:

[0037] The sodium battery precursor Ni0.33Fe0.33Mn0.34(OH)2, sodium salt Na2CO3, CuO and Al2O3 prepared by co-precipitation method were evenly mixed in a stoichiometric ratio of 1:0.5:0.01:0.005, and then the mixture was loaded into a corundum sagger and transferred to a high-temperature box furnace. The first stage calcination temperature was 500℃, the time was 5h, and the heating rate was 4℃ / min. The second stage calcination temperature was 900℃, the time was 15h, and the heating rate was 4℃ / min. The calcination atmosphere in both stages was oxygen. After cooling in the furnace, the O3 type layered oxide sodium ion battery positive electrode material NaNi0.32Fe0.32Mn0.34Cu0.01Al0.01O2 was obtained.

[0038] The sodium battery precursor Ni0.25Fe0.25Mn0.50(OH)2, sodium salt Na2CO3, CaO and Co2O3 prepared by co-precipitation method were evenly mixed in a stoichiometric ratio of 1:0.35:0.01:0.005, and then the mixture was loaded into a corundum sagger and transferred to a high-temperature box furnace. The first stage calcination temperature was 500°C, the time was 5h, and the heating rate was 4°C / min. The second stage calcination temperature was 900°C, the time was 15h, and the heating rate was 4°C / min. The calcination atmosphere in both stages was oxygen. After cooling in the furnace, the P2 type layered oxide sodium ion battery positive electrode material Na0.7Ni0.24Fe0.24Mn0.50Ca0.01Co0.01O2 was obtained.

[0039] Take 55g of each of the two layer oxygen materials, O3 phase NaNi0.32Fe0.32Mn0.34Cu0.01Al0.01O2 and P2 phase Na0.7Ni0.24Fe0.24Mn0.50Ca0.01Co0.01O2, and mix them evenly with 3.6g of potassium molybdate, and then sinter them. First, keep them at 900℃ for 6h and then keep them at 950℃ for 8h. After cooling, the finished material Na0.85K0.03(Ni0.28Fe0.28Mn42Cu0.005Al0.005Ca0.005Co0.005)0.985Mo0.015O2 is obtained.

[0040] The finished material was subjected to XRD analysis, such as Figure 2 As shown, it is confirmed that Q=16.247-15.973=0.274.

[0041] The finished materials were assembled into secondary batteries, and their electrochemical properties were measured and shown in Table 1. Embodiment 2:

[0042] The precursor obtained by co-precipitation method is mixed with sodium salt and dopant, and sintered at 870°C to form two kinds of layered oxide materials, Na0.9Ni0.35Fe0.2Mn0.4Cu0.03Zn0.02O2 of O3 phase and Na0.74Ni0.2Fe0.1Mn0.65Mg0.05O2 of P2 phase, respectively. 55g of each of these two layered oxide materials is mixed evenly with 4.8g of potassium molybdate and sintered, first kept at 875°C for 8h and then kept at 935°C for 12h. After cooling, the finished material Na0.82K0.04(Ni0.27Fe0.15Mn0.52Cu0.01Zn0.01Mg0.02)0.98Mo0.02O2 is obtained.

[0043] The finished material was subjected to XRD analysis, such as Figure 3 As shown, it is confirmed that Q=16.206-15.919=0.287.

[0044] The finished materials were assembled into secondary batteries, and their electrochemical properties were measured and shown in Table 1. Embodiment 3:

[0045] The precursor obtained by co-precipitation method is mixed with sodium salt and dopant, and sintered at 950°C to form two layered oxide materials, Na0.97 Ni0.30Fe0.30Mn0.34Cu0.02Ti0.02O2 of O3 phase and Na0.79Ni0.24Fe0.2Mn0.5Mg0.05Nb0.01O2 of P2 phase, respectively. 55g of each of these two layered oxide materials is mixed evenly with 2.4g of potassium molybdate and sintered, first kept at 850°C for 10h, and then kept at 950°C for 10h. After cooling, the finished material Na0.88K0.02(Ni0.27Fe0.25Mn0.42Cu0.01Ti0.01Mg0.025Nb0.005)0.99Mo0.01O2 is obtained.

[0046] The finished material was subjected to XRD analysis, such as Figure 4 As shown, it is confirmed that Q=16.499-16.369=0.130.

[0047] The finished materials were assembled into secondary batteries, and their electrochemical properties were measured and shown in Table 1.

[0048] Comparative Example 1:

[0049] The precursor obtained by co-precipitation method is mixed with sodium salt and dopant, and sintered at 900°C into two layered oxide materials, NaNi0.32Fe0.32Mn0.33Cu0.01Al0.01O2 of O3 phase and Na0.7Ni0.24Fe0.24Mn0.50Ca0.01Co0.01O2 of P2 phase, respectively. 55g of each of these two layered oxide materials are mixed evenly and sintered, first kept at 900°C for 6h and then kept at 950°C for 8h. After cooling, the finished material Na0.85Ni0.29Fe0.28Mn41Cu0.005Al0.005Ca0.005Co0.005O2 is obtained.

[0050] The finished material was subjected to XRD analysis, such as Figure 5 As shown, it is confirmed that Q=16.28-15.961=0.319.

[0051] The finished materials were assembled into secondary batteries, and their electrochemical properties were measured and shown in Table 1.

[0052] Comparative Example 2:

[0053] The precursor obtained by co-precipitation method is mixed with sodium salt and dopant, and sintered at 870°C to form two kinds of layered oxide materials, Na0.9Ni0.35Fe0.2Mn0.4Cu0.03Zn0.02O2 of O3 phase and Na0.74Ni0.2Fe0.1Mn0.65Mg0.05O2 of P2 phase, respectively. 55g of each of these two layered oxide materials are mixed evenly with 4.8g of potassium molybdate and sintered, and kept at 875°C for 20h. After cooling, the finished material Na0.82K0.04(Ni0.27Fe0.15Mn0.52Cu0.01Zn0.01Mg0.02)0.98Mo0.02O2 is obtained.

[0054] The finished material was subjected to XRD analysis, such as Figure 6 As shown, it is confirmed that Q=16.391-15.959=0.432.

[0055] The finished materials were assembled into secondary batteries, and their electrochemical properties were measured and shown in Table 1.

[0056] Comparative Example 3:

[0057] The precursor obtained by co-precipitation method is mixed with sodium salt and dopant, and sintered at 870°C to form two kinds of layered oxide materials, Na0.9Ni0.35Fe0.2Mn0.4Cu0.03Zn0.02O2 of O3 phase and Na0.74Ni0.2Fe0.1Mn0.65Mg0.05O2 of P2 phase, respectively. 55g of each of these two layered oxide materials are mixed evenly with 4.8g of potassium molybdate and sintered, and kept at 935°C for 20h. After cooling, the finished material Na0.82K0.04(Ni0.27Fe0.15Mn0.52Cu0.01Zn0.01Mg0.02)0.98Mo0.02O2 is obtained.

[0058] The finished material was subjected to XRD analysis, confirming that Q=16.372-15.977=0.395.

[0059] The finished materials were assembled into secondary batteries, and their electrochemical properties were measured and shown in Table 1.

[0060] Comparative Example 4:

[0061] The precursor obtained by co-precipitation method is mixed with sodium salt and dopant, and sintered at 900°C into two layered oxide materials, NaNi0.32Fe0.32Mn0.33Cu0.01Al0.01O2 of O3 phase and Na0.7Ni0.24Fe0.24Mn0.50Ca0.01Co0.01O2 of P2 phase, respectively. 55g of each of these two layered oxide materials is mixed evenly with 3.7g of magnesium molybdate and sintered, first kept at 900°C for 6h and then kept at 950°C for 8h. After cooling, the finished material Na0.85Mg0.02(Ni0.28Fe0.28Mn42Cu0.005Al0.005Ca0.005Co0.005)0.98Mo0.02O2 is obtained.

[0062] The finished material was subjected to XRD analysis, confirming that Q=16.503-16.058=0.445.

[0063] The finished materials were assembled into secondary batteries, and their electrochemical properties were measured and shown in Table 1.

[0064] Comparative Example 5:

[0065] The precursor obtained by co-precipitation method is mixed with sodium salt and dopant, and sintered at 870°C to form two kinds of layered oxide materials, Na0.9Ni0.35Fe0.2Mn0.4Cu0.03Zn0.02O2 of O3 phase and Na0.74Ni0.2Fe0.1Mn0.65Mg0.05O2 of P2 phase, respectively. 55g of each of these two layered oxide materials is mixed evenly with 6.5g of potassium tungstate and then sintered, first kept at 875°C for 8h and then kept at 935°C for 12h. After cooling, the finished material Na0.82K0.04(Ni0.27Fe0.15Mn0.52Cu0.01Zn0.01Mg0.02)0.98W0.02O2 is obtained.

[0066] The finished material was subjected to XRD analysis and confirmed to have Q=16.352-15.984=0.368.

[0067] The finished materials were assembled into secondary batteries, and their electrochemical properties were measured and shown in Table 1.

[0068] Comparative Example 6:

[0069] The precursor obtained by co-precipitation method is mixed with sodium salt and dopant, and sintered at 950°C to form two layered oxide materials, Na0.97Ni0.30Fe0.30Mn0.34Cu0.02Ti0.02O2 of O3 phase and Na0.79Ni0.24Fe0.2Mn0.5Mg0.05Nb0.01O2 of P2 phase, respectively. 55g of each of these two layered oxide materials is mixed evenly with 14.4g of potassium molybdate and sintered, first kept at 850°C for 10h, and then kept at 950°C for 10h. After cooling, the finished material Na0.88K0.12(Ni0.27Fe0.25Mn0.42Cu0.01Ti0.01Mg0.025Nb0.005)0.94Mo0.06O2 is obtained.

[0070] The finished material was subjected to XRD analysis, such as Figure 4 As shown, it is confirmed that Q=16.219-15.732=0.487.

[0071] The finished materials were assembled into secondary batteries, and their electrochemical properties were measured and shown in Table 1.

[0072] Comparative Example 7:

[0073] The precursor obtained by co-precipitation method is mixed with sodium salt and dopant, and sintered at 900°C into two layered oxide materials, NaNi0.32Fe0.32Mn0.33Cu0.01Al0.01O2 of O3 phase and Na0.7Ni0.24Fe0.24Mn0.50Ca0.01Co0.01O2 of P2 phase, respectively. 55g of each of these two layered oxide materials is mixed evenly with 1.2g of potassium molybdate and sintered, first kept at 900°C for 6h and then kept at 950°C for 8h. After cooling, the finished material Na0.85K0.01(Ni0.28Fe0.28Mn42Cu0.005Al0.005Ca0.005Co0.005)0.98Mo0.005O2 is obtained.

[0074] The finished material was subjected to XRD analysis and confirmed to have Q=16.483-16.128=0.355.

[0075] The finished materials were assembled into secondary batteries, and their electrochemical properties were measured and shown in Table 1.

[0076] Table 1 Battery performance in Examples 1-3 and Comparative Examples 1-7

[0077] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.

[0078] It should be understood that the technical solution of the present invention is not limited to the above-mentioned specific implementation cases. Any technical deformation made according to the technical solution of the present invention without departing from the scope of protection of the purpose of the present invention and the claims shall fall within the protection scope of the present invention.

Claims

1. A sodium ion battery positive electrode material, characterized in that: include: The sodium layer is composed of a P2 phase material containing potassium and a transition metal layer is composed of an O3 phase material containing molybdenum, and the layer adaptability of the sodium ion battery positive electrode material is Q≤0.3, and Q=|q1-q2|; In which, when the sodium ion battery positive electrode material is tested by XRD, the [002] peak of the P2 phase material corresponds to an angle 2θ of q1, and the [003] peak of the O3 phase material corresponds to an angle 2θ of q2.

2. The sodium ion battery positive electrode material according to claim 1, characterized in that: The chemical formula of the sodium ion battery positive electrode material is Na x K y (Ni a1 Fe b1 Mn c1 M1 d1 ) 1-d2 Mo d2 O2, wherein (a1+b1+c1+d1)=1, 0.8≤x+y≤0.95, M1 is selected from any one or more combinations of elements selected from Sn, Fe, Al, Nb, Ti, Zr, Sr, Co, Li, K, Mg, Ca, Cu, Zn, 0.25≤a1≤0.4, 0.15≤b1≤0.4, 0.3≤c1≤0.55, 0.01≤d1≤0.05, 0.01≤d2≤0.05, y=2*d2.

3. The method for preparing a positive electrode material for a sodium ion battery according to claim 1 or 2, characterized in that: include: At least a nickel-iron-manganese hydroxide precursor, a sodium source, and an M1 source are used as raw materials to prepare an O3-type layered oxide positive electrode material and a P2-type layered oxide positive electrode material; And, the O3 type layered oxide positive electrode material, the P2 type layered oxide positive electrode material and potassium molybdate are mixed and sintered to obtain a sodium ion battery positive electrode material.

4. The preparation method according to claim 3, characterized in that: Specifically include: The nickel iron manganese hydroxide precursor, the sodium source and the M1 source are mixed and sintered at 850-950° C. for 12-24 hours to prepare an O3 type layered oxide positive electrode material and a P2 type layered oxide positive electrode material; Wherein, the chemical formula of the O3 type layered oxide positive electrode material is Na x Ni a1 Fe b1 Mn c1 M1 d1 O2, 0.80<x≤1.0, 0.25≤a1≤0.4, 0.25≤b1≤0.4, 0.3≤c1≤0.55, 0.01≤d1≤0.05; the chemical formula of the P2-type layered oxide positive electrode material is Na x Ni a1 Fe b1 Mn c1 M1 d1 O2, 0.60≤x≤0.80, 0.25≤a1≤0.4, 0.25≤b1≤0.4, 0.3≤c1≤0.55, 0.01≤d1≤0.

05.

5. The preparation method according to claim 3, characterized in that: The nickel-iron-manganese hydroxide precursor is prepared by using any one or more combinations of sulfates, hydrochlorides, nitrates, carbonates, acetates, oxides, sulfides, nitrides, and hydroxides of nickel-iron-manganese ions; And / or, the sodium source includes any one or more combinations of anhydrous sodium carbonate, sodium carbonate monohydrate, sodium carbonate decahydrate, sodium bicarbonate, and sodium sulfate; And / or, the M1 source is selected from the corresponding oxides and / or hydroxides of any one or more combinations of Sn, Fe, Al, Nb, Ti, Zr, Sr, Co, Li, K, Mg, Ca, Cu, and Zn.

6. The preparation method according to claim 3, characterized in that: Specifically include: The O3 type layered oxide positive electrode material, the P2 type layered oxide positive electrode material and potassium molybdate are uniformly mixed, first sintered at 850-910° C. for 4-12 hours, and then sintered at 920-1000° C. for 4-12 hours to obtain the sodium ion battery positive electrode material.

7. The preparation method according to claim 3, characterized in that: The mass ratio of the O3 type layered oxide positive electrode material, the P2 type layered oxide positive electrode material and potassium molybdate is 0.2-0.8:0.8-0.2:0.01-0.

05.

8. Use of the sodium ion battery positive electrode material according to claim 1 or 2 in preparing a sodium battery positive electrode or a sodium ion battery.

9. A sodium battery positive electrode, characterized in that: It comprises a positive electrode material, a conductive agent, a binder and a current collector; wherein the positive electrode material comprises the positive electrode material for a sodium ion battery according to claim 1 or 2.

10. A sodium ion battery, characterized in that: The invention comprises the sodium ion battery positive electrode material according to any one of claims 1 to 2 or the sodium battery positive electrode according to claim 9.